Financial determinants of firm value in telecommunications companies: evidence from the Indonesian stock exchange - Eva Romauli; Suhardi Suhardi; Rita Deseria (Economic: Journal Economic and Business, 2026)
This study aims to analyze the effect of company size, capital structure, liquidity, and profitability on firm value in telecommunications companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with panel data regression analysis. The research sample consisted of 19 telecommunications companies with a total of 95 observations selected using a purposive sampling technique. The analytical method used is the Fixed Effect Model based on the results of the Chow and Hausman test. Firm value is measured using Price to Book Value, firm size using total assets, capital structure using the Debt to Equity Ratio, liquidity using the Current Ratio, and profitability using Return on Equity. The results show that liquidity has a negative and significant effect on firm value, while firm size, capital structure, and profitability have no significant effect. Simultaneously, all independent variables affect firm value. These findings indicate that investors in the telecommunications sector pay more attention to the efficiency of liquidity management and financial stability in assessing companies. This study provides implications for company management in optimizing financial policies to increase firm value.